2018
DOI: 10.1016/j.cels.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Correlated Gene Expression in Bacterial Groups: The Role of Lineage History, Spatial Gradients, and Cell-Cell Interactions

Abstract: Gene expression levels in clonal bacterial groups have been found to be spatially correlated. These correlations can partly be explained by the shared lineage history of nearby cells, although they could also arise from local cell-cell interactions. Here, we present a quantitative framework that allows us to disentangle the contributions of lineage history, long-range spatial gradients, and local cell-cell interactions to spatial correlations in gene expression. We study pathways involved in toxin production, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 68 publications
3
71
0
Order By: Relevance
“…First, plasmid copy number variation could lead to overestimate the variation in gene expression between cells. However, previous work has shown that for most promoters copy number variation of the reporter plasmids we used is negligible compared to variation in transcriptional activity [33,34]. Second, because (fluorescent) proteins have long lifetimes, fluorescent intensities in cells do not only depend on current, but also on past, transcriptional activity.…”
Section: Resultsmentioning
confidence: 98%
“…First, plasmid copy number variation could lead to overestimate the variation in gene expression between cells. However, previous work has shown that for most promoters copy number variation of the reporter plasmids we used is negligible compared to variation in transcriptional activity [33,34]. Second, because (fluorescent) proteins have long lifetimes, fluorescent intensities in cells do not only depend on current, but also on past, transcriptional activity.…”
Section: Resultsmentioning
confidence: 98%
“…Verifying the proportion of SAR11 cells actively dividing in a culture may be challenging. Time-lapse microscopy (135) offers an elegant solution if SAR11 can be maintained for the requisite time periods for accurate measurements in a microfluidic device.…”
Section: Discussionmentioning
confidence: 99%
“…Growth rates were log transformed. GFP_vecfw 5' CAC TGG AGT TGT CCC AAT TCT TGT TG pSV66-rpsM-gfp-rpsM-rfp [3] RFP_vec-rv 5' ATG AGC GAG CTG ATC AAG G pSV66-rpsM-gfp-rpsM-rfp [3] GFP_vec-rv 5' GTT TCT TAG ACG TCG GAA TTG CCA G pSV66-rpsM-gfp-rpsM-rfp [3] RFP_vecfw 5' CTG TTC TGG TGT TGC TAG TTT G pSV66-rpsM-gfp-rpsM-rfp [3] Supplemental references…”
Section: Supplemental Moviementioning
confidence: 99%